Contrasting the Perception and Response of Domestic Manufacturing Firms to FDI in Sub-Saharan Africa - Penélope Pacheco-López (University of Kent, School of Economics, 2014)
This paper uses the data set from the fourth survey by UNIDO of manufacturing firms in Sub-Saharan Africa to identify whether foreign direct investment affects the behaviour of local firms with respect to investment, product innovation and process innovation. We look at the perception and response of 1,140 manufacturing firms in 9 sectors in 19 countries. Using Probit models the results suggest that, once controlling for firm's characteristics, there is a marked difference between perception and reality. The presence of foreign investment has not affected the behaviour of the vast majority of domestic firms in terms of their investment, production of similar products to foreign firms, production of different products to avoid competition or adopt similar production technologies.
Keywords: O14; O31; O55; 330; FDI; investment; technology; Sub-Saharan African countries